Thermochemical energy storage performance of papermaking soda residue during CaO-CaCO3 cycles. (August 2022) - Li, Caili; Li, Yingjie; Zhang, Chunxiao; Dou, Yehui; Xu, Yunfei; Zhao, Jianli
Abstract: Papermaking soda residue (PSR) is calcium-rich waste produced by the papermaking industry. In this study, the thermochemical energy storage performances of the original PSR and PSR modified with citric acid were investigated under pressurised carbonation during CaO-CaCO3 cycles in a twin fixed-bed reactor. The effects of carbonation pressure, reaction temperatures, and number of cycles on the energy storage performance were also discussed. The modified PSR exhibits higher energy storage capacity than the original PSR. The energy storage performances of the two PSRs are improved with increasing carbonation pressure from 0.1 to 1.1 MPa. The energy storage density and effective conversion of the modified PSR at 1.1 MPa are approximately 2210 kJ·kg -1 and 0.7 after 30 cycles, respectively. The energy storage density of the modified PSR at 1.1 MPa is approximately 156% greater than that of the original PSR at 0.1 MPa. Carbonation and calcination temperatures of 850 °C are suitable for the energy storage of both PSRs. The surface area and pore volume of the modified PSR are 1.84 and 1.75 times those of the original PSR, respectively. The modified PSR is a suitable energy storage material. Highlights: PSR as a calcium-rich waste from paper mills is proposed as energy storage material. Modification with citric acid markedly improves the energy storage capacity of PSR. Modified PSR has high energy storage capacity under 1.1 MPa. Modified PSR maintains porous and stable structure in energy storage cycles.